Association between short-term exposure to air pollution and ischemic stroke: A case-crossover study in China. (15th August 2022) - Wu, Mengyin; Yu, Luhua; Li, Tiezheng; Lu, Jieming; Yang, Zongming; Shen, Peng; Tang, Mengling; Jin, Mingjuan; Lin, Hongbo; Chen, Kun; Wang, Jianbing
Abstract: Objective: To examine the association between short-term exposure to air pollution and ischemic stroke (IS) onset and the role of lifestyles on the association. Methods: We performed a time-stratified case-crossover study to estimate the association between short-term exposure to air pollution and IS onset in Yinzhou, China from July 1st, 2015 to May 31st, 2020. Conditional logistic regression models were used to assess the effect of air pollution on IS onset. Furthermore, we explored whether these effects were modified by lifestyle factors by using stratified analyses. Results: A total of 700 subjects were included in analyses. We found that positive associations between exposure to O3 and IS onset with the ORIQRs of 1.23 (95% CI: 1.01–1.49) at lag04 and 1.28 (95% CI: 1.03–1.59) at lag06, respectively. Stronger associations were observed between NO2 at lag04 and lag06 and IS onset after adjusting for other air pollutants, and the corresponding ORIQRs were 2.08 (95% CI: 1.37–3.15) and 2.04 (95% CI: 1.27–3.27), respectively. However, no association was observed for exposure to particulate matters and IS onset. Stronger associations were observed for NO2 and risk of IS onset among abnormal weight subjects, alcohol drinkers, smokers, and subjects who exercised 1–4 times per week or barely exercised every week. We also observed stronger associations of SO2, CO, PM2.5 and PM10 with IS onset among subjects who exercised 1–4 times per week. Conclusions: In this case-crossover study, we found positive associations between short-term exposure to air pollution, especially for NO2, and risk of IS onset. Moreover, our study highlighted that lifestyle factors, such as alcohol consumption and physical activity, had significant impacts on the association of ambient air pollution with risk of IS onset. Highlights: New evidence on the association between short-term exposure to air pollution and ischemic stroke from China. O3 and NO2 were positively associated with risk of ischemic stroke onset. Lifestyle factors could affect the association of short-term exposure to air pollution with risk of ischemic stroke onset.